2020
DOI: 10.1080/03007995.2020.1841618
|View full text |Cite
|
Sign up to set email alerts
|

The burden of disease in early schizophrenia – a systematic literature review

Abstract: Background: Schizophrenia is a heterogeneous disorder with a burden that can vary greatly depending on the severity and the duration. Previous research has suggested that patients in the earlier stages of schizophrenia (typically first-episode schizophrenia) benefit from effective early treatment, however, a comprehensive review of the burden specifically in this population has not been undertaken. A systematic literature review was therefore conducted to characterize the clinical, economic, and humanistic bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 77 publications
2
33
0
Order By: Relevance
“…One aspect meriting attention is the finding that the most common social benefit received before SA < 90 days due to mental diagnoses was unemployment benefits. This might reflect the higher level of unemployment among workers with mental disorders (Crespo-Facorro et al 2021;Drake and Wallach 2020;McAlpine and Alang 2021), but further studies should address this in detail.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect meriting attention is the finding that the most common social benefit received before SA < 90 days due to mental diagnoses was unemployment benefits. This might reflect the higher level of unemployment among workers with mental disorders (Crespo-Facorro et al 2021;Drake and Wallach 2020;McAlpine and Alang 2021), but further studies should address this in detail.…”
Section: Discussionmentioning
confidence: 99%
“…We enjoyed reading the recent article entitled, "The burden of disease in early schizophrenia -a systematic literature review" by Crespo-Facorro et al published in this journal 4 . The authors demonstrated the presence of multiple burdens in patients with schizophrenia compared with healthy controls, including increased mortality, psychiatric comorbidities, such as substance abuse and depression, poor social integration and functioning, and increased levels of unemployment 4 . Despite the clinical and epidemiological relevance of this study 4 , we would like to add some thoughts about the possible role of sudden unexpected death in schizophrenia (SUDS).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The authors demonstrated the presence of multiple burdens in patients with schizophrenia compared with healthy controls, including increased mortality, psychiatric comorbidities, such as substance abuse and depression, poor social integration and functioning, and increased levels of unemployment 4 . Despite the clinical and epidemiological relevance of this study 4 , we would like to add some thoughts about the possible role of sudden unexpected death in schizophrenia (SUDS). 2,3 Patients with schizophrenia have a 2 to 3-fold increased risk to die prematurely compared with those without this mental illness 2,3 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Schizophrenia (SZ) is a neuropsychiatric disorder imposing a significant personal and socioeconomic burden (1). Understanding the neuropathological processes underlying SZ has been hampered by the neurobiological heterogeneity of this disorder (2, 3), which has confounded case-control studies and impeded progress in treatment development (4).…”
Section: Introductionmentioning
confidence: 99%